2017
DOI: 10.1136/bmjopen-2017-017453
|View full text |Cite
|
Sign up to set email alerts
|

Consensus validation of the POSAMINO (POtentially Serious Alcohol–Medication INteractions in Older adults) criteria

Abstract: ObjectivesOlder adults are particularly vulnerable to adverse effects from concurrent alcohol and medication use. However, there is limited evidence regarding the prevalence of these adverse outcomes among older adults, and there is a lack of consensus regarding what constitutes an alcohol-interactive medicine. The objective of this study was to develop an explicit list of potentially serious alcohol–medication interactions for use in older adults.DesignFollowing a systematic review, review of drug compendia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“… 34 35 A study of 844 current drinkers aged 65–74 years in Australia found that older men poured drinks that were 32% larger than a standard drink of 10 g alcohol, with older women pouring drinks that were 16% larger. 36 Furthermore, in the absence of internationally agreed age-specific drinking guidelines, we used national Irish recommendations to define heavy alcohol consumption in the development of the POSAMINO criteria 9 and in this study to classify participants as heavy drinkers. Given that older adults are more vulnerable to harm even at low levels of alcohol consumption, our estimates of POSAMINO may reflect an underestimate of the true prevalence among older adults particularly for those criteria involving heavy alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“… 34 35 A study of 844 current drinkers aged 65–74 years in Australia found that older men poured drinks that were 32% larger than a standard drink of 10 g alcohol, with older women pouring drinks that were 16% larger. 36 Furthermore, in the absence of internationally agreed age-specific drinking guidelines, we used national Irish recommendations to define heavy alcohol consumption in the development of the POSAMINO criteria 9 and in this study to classify participants as heavy drinkers. Given that older adults are more vulnerable to harm even at low levels of alcohol consumption, our estimates of POSAMINO may reflect an underestimate of the true prevalence among older adults particularly for those criteria involving heavy alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…An international consensus project, using a Delphi methodology could be organised to reach consensus regarding the most clinically appropriate definition of retention. The Delphi methodology allows a consensus opinion to be reached among a panel of experts through an interactive process of questionnaires [108]. A pooled analysis of individual level data from multiple cohorts, particularly those using similar methods to ascertain outcome such as prescription refill data, could also be undertaken to inform an internationally agreed definition.…”
Section: Clinical Implications and Areas For Future Researchmentioning
confidence: 99%
“…5 Interactions can occur across a range of common medications for long term conditions, including cardiovascular diseases, pain, depression, diabetes, musculoskeletal conditions, infections, and cancer. 6 Medications that interact with alcohol are widely prescribed to people who drink alcohol. 7 Alcohol can also have a direct and adverse effect on many conditions for which medications are prescribed, even when consumption is lower than that which is defined as low risk in drinking guidelines.…”
Section: Health Risksmentioning
confidence: 99%